SAT0351 Calcium/vitamin D supplements do not deteriorate the increased vascular calcification in osteoporotic women. (23rd January 2014) - Lampropoulos, C.E.; Konsta, M.; Kalamara, P.; Papaioannou, I.; Niarou, V.; Iliopoulou, E.; Iliopoulos, A.
Abstract : Background: Vascular calcification (VC) is an independent risk factor for cardiovascular disease (CVD). 1 Many articles revealed common pathogenetic mechanisms between osteoporosis and VC, suggesting a causative role of osteoporosis in VC. 2 An important issue was raised recently about the safety of calcium/vitamin D supplements and their influence on VC and CVD. 3, 4 Objectives: To estimate the correlation between osteoporosis and VC in post-menopausal women and the influence of calcium/vitamin D supplements on VC. Methods: A case-control study was performed including 29 women with osteoporosis (15 without supplements) and 18 with normal BMD (mean age 59.5±6.3). Patients were evaluated for cardiovascular risk factors: hypertension, smoking, diabetes, dyslipidemia, obesity, drinking habits, MedDiet score and IPAQ score. Patients performed blood tests (glucose, renal function, lipid profile, CRP), carotids' ultrasound [intima media thickness (IMT, abnormal when >0.8mm) or calcified plaques], heart ultrasound and lateral x-ray of lumbar spine for abdominal aortic calcification (AAC) (range 0-24, abnormal when score ≥2). Clinical and demographic variables of patients were compared for categorical and continuous variables. Odds ratios (OR) were calculated and logistic regression analysis was performed to identify independent predictors for VC. Results: In group with osteoporosis, 13/29 women had AAC and 22/29 increased IMT or plaques compared to 1/18 and 5/18 of non-osteoporotic women respectively. Osteoporotic women are 14 times more likely to develop AAC (OR=13.8, p=0.016) and 7.7 times increased IMT (OR=7.7, p=0.003), compared to non-osteoporotic. The odds of developing AAC are increased 14% per year after menopause (OR=1.14, p=0.009) and 37% per year increase (OR=1.37, p=0.001). Similarly, the odds of increased IMT are increased 17% per year after menopause (OR=1.17, p=0.006) and 18% per year increase (OR=1.18, p=0.008). The odds of developing AAC are 4-fold increased (OR=4.1, p=0.05) per each unit increase of calcium in serum. Comparison of cardiovascular risk factors between the 2 groups revealed no significant differences. Calcium/vitamin D supplements didn't aggravate AAC or IMT as there were no differences between the 2 subgroups of osteoporotic women (8/15 of women without supplements had AAC and 12/15 increased IMT compared to 5/14 and 10/14 of women with supplements respectively). Conclusions: Osteoporosis is related with increased VC of abdominal aorta and carotids. This finding is in accordance with previous studies where osteoporosis is associated with AAC and increased IMT. 5, 6 Calcium/vitamin D supplements do not deteriorate VC in osteoporotic women. Further studies are needed to establish osteoporosis as a cardiovascular risk factor and evaluate the role of supplements in osteoporosis treatment. References: Rennenberg RJ, et al. Vasc Health Risk Manag 2009;5:185-97 Rajamannan NM, et al. Circulation 2003;107:2181-4 Hsia J, et al. Circulation 2007;115:846-54 Lewis JR, et al. J Bone Miner Res 2011;26:35-41 Kiel DP, et al. Calcif Tissue Int 2001;68:271-6 Sumino H, et al. Hypertens Res 2008;31:1191-7 Disclosure of Interest: None Declared